(untitled) (International Seven Journal of Health Research, 2023)
Osteomyelite, an infectious orthopedic pathology, constitutes a challenge for physicians orthopedic surgery, but it is difficult to program a valid therapeutic algorithm for each clinical situation, making it imperative to investigate the various aspects related to Its pathophysiology, and the most appropriate treatment protocol Despite several studies We Will demonstrate good results with the available techniques, there is no single approach consensual not that it says respect to the treatment of osteomyelite. In this way, the protocols medical and surgical, complement each other, hair that frequently num doente, is tour both. Cleaning and removing shaved tissue are the first steps of any treatment. Antibiotic medical therapy should be performed in infectious osteomyelites acute, subacute and chronic. Surgical therapy consists of lengthening debridement, Sequestrectomy and, if necessary, subsequent stabilization with a bone graft and coverage with known moles. Therapeutics of CRMO aims to control autoimmunity. DOI:https://doi.org/10.56238/isevjhv2n2-012